2012
DOI: 10.1371/journal.pone.0035516
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Actively Inhibits Neuronal Function in Chronically Infected Mice

Abstract: Upon infection with the obligate intracellular parasite Toxoplasma gondii, fast replicating tachyzoites infect a broad spectrum of host cells including neurons. Under the pressure of the immune response, tachyzoites convert into slow-replicating bradyzoites, which persist as cysts in neurons. Currently, it is unclear whether T. gondii alters the functional activity of neurons, which may contribute to altered behaviour of T. gondii–infected mice and men. In the present study we demonstrate that upon oral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 31 publications
6
79
1
Order By: Relevance
“…Indeed, recent studies that have analyzed the frequency of neurological symptoms in mice used strains such as C57BL/6 (22, 23), CD1 (24), and SW (3) at 6 to 18 weeks postinfection. Some researchers have used BALB/c mice to analyze behavior changes in the mice at 2 and 6 months after T. gondii infection (5,25). Therefore, the mouse model of T. gondii infection in BALB/c mice used in the present study could be used for evaluating toxoplasmosis at an earlier stage after infection than in the studies described above.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, recent studies that have analyzed the frequency of neurological symptoms in mice used strains such as C57BL/6 (22, 23), CD1 (24), and SW (3) at 6 to 18 weeks postinfection. Some researchers have used BALB/c mice to analyze behavior changes in the mice at 2 and 6 months after T. gondii infection (5,25). Therefore, the mouse model of T. gondii infection in BALB/c mice used in the present study could be used for evaluating toxoplasmosis at an earlier stage after infection than in the studies described above.…”
Section: Discussionmentioning
confidence: 97%
“…This effect was related to T. gondii orchestration of a significant increase in dopamine metabolism via tyrosine hydroxylase production, which is the rate-limiting enzyme for dopamine synthesis in neural cells (35). Furthermore, in vitro experiments demonstrated that tachyzoites actively prevented the normal Ca 2ϩ responses of glutamate-stimulated neurons; hence, it was suggested that T. gondii infects neurons and may directly modulate neuronal function (5). In this study, genes that were identified as being negatively correlated with parasite numbers were involved in small-GTPase-mediated signal transduction and GTP or guanyl nucleotide binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, infection causes lowlevel inflammation throughout the brain (45), affects the activity level of infected neurons (46), alters microRNA expression in cells (35), and causes changes in host gene expression in the frontal cortex of mice (12). Since chronic infection leads to activated microglia around many, but not all, tissue cysts (47), a potential cause of signaling and behavioral abnormalities would be inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a control of the infection but also creates a hospitable environment assuring the parasite's long-term survival. The chronic phase of infection is characterized by numerous intact T. gondii cysts scattered throughout the whole brain being able, thus, to alter directly or indirectly neuronal function and presumably the behavior [49,50].…”
Section: Introductionmentioning
confidence: 99%